Comparative Analysis of Embedded Systems for Mobile Health Applications Against Cyber Attacks: A Review Study - Anayo Chukwu Ikegwu; Excellence Essien Akparawa; Uzoma Rita Alo (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
Mobile health applications and embedded systems have transformed healthcare by offering real-time monitoring, remote diagnostics, and better patient outcomes. However, reliance on digital health solutions introduces significant cybersecurity challenges, requiring robust security measures to protect sensitive patient data. This paper discusses the security needs of embedded systems in mHealth, emphasizing the importance of confidentiality, integrity, and availability to safeguard data. It reviews compliance frameworks such as HIPAA and GDPR, which set data protection standards. The research highlights the need for cybersecurity to support patient safety, mitigate risks after device compromise, and defend against emerging threats. Comparative studies of current security technologies, both hardware- and software-based, show their impact against cyberattacks. Finally, the paper discusses trends such as AI-driven threat detection, post-quantum cryptography, and edge computing as future mHealth security paradigms. By adopting strong security protocols, healthcare institutions can boost trust, meet regulations, and secure mHealth embedded systems.